2018
DOI: 10.1016/j.ihj.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal positions relative to the left atrium; data from 293 patients before catheter ablation of atrial fibrillation

Abstract: The position of the esophagus to the LA is highly variable. The most common position of the esophagus relative to the LA is behind the middle and left part of the posterior wall of the LA. The least frequently observed position is behind the right pulmonary veins. No significant position change of esophagus motion from before to after the ablation procedure in the majority (≥95%) of the patients was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Another study found that esophageal position was relatively stable before and after ablation using 3D rotational angiography for the PVs and visualization of the esophagus via peroral administration of a contrast agent. 14 However, whether esophageal movement is stimulated by the swallowing of barium and whether general anesthesia has any influence on esophageal motility with a postulated hypothesis that the esophagus has a resting position are unknown. Real-time observation of the esophageal position is feasible with intracardiac echocardiography, but this costly option is not widely available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that esophageal position was relatively stable before and after ablation using 3D rotational angiography for the PVs and visualization of the esophagus via peroral administration of a contrast agent. 14 However, whether esophageal movement is stimulated by the swallowing of barium and whether general anesthesia has any influence on esophageal motility with a postulated hypothesis that the esophagus has a resting position are unknown. Real-time observation of the esophageal position is feasible with intracardiac echocardiography, but this costly option is not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Sherzer et al, found a stability of the esophageal position relative to the spine by means of an ablation catheter in the esophagus during the whole procedure in patients under general anesthesia 13 . Another study found that the esophageal position was relatively stable before and after ablation using 3D rotational angiography for the PVs and visualization of the esophagus via peroral administration of a contrast agent 14 . Yet, it is unknown if the esophageal movement is stimulated by the swallowing of barium and whether general anesthesia has any influence on esophageal motility with a postulated hypothesis that the esophagus has a resting position.…”
Section: Stability Of the Esophageal Position During The Same Proceduresmentioning
confidence: 99%
“…The importance here, is that images acquired up to 30 days before the procedure, provide important and relevant anatomical information regarding esophageal location relative to the left atrium and pulmonary vein antra. Although data regarding esophageal stability overtime are conflicting, 17–19 it is likely that any esophageal movement in the posterior left atrium region is minimal, related to peristalsis, and unlikely to constrain the utility of preacquired images. A prior study by Sarairah et al 20 found that endoscopically detected esophageal thermal lesions were negatively associated with the shortest distance between the esophageal lumen and the atrial endocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Metoda je výrazně účinnější než farmakologické strategie a stala se metodou první volby v léčbě této arytmie (13)(14)(15). Postupně byla zapojena celá řada metod zvyšujících účinnost a bezpečnost RFA (16)(17)(18)(19)(20)(21). KA byla následně doplněna dalšími technologiemi jako například kryoablace (22) či laserové ablace (23), které jsou obdobně jako RFA založené na termálním faktoru v tvorbě ablačních lézí.…”
Section: úVodunclassified